A Pandemic Instrument can Optimize the Regime Complex for AMR by Striking a Balance between Centralization and Decentralization. (2022) - Weldon, Isaac; Yaseen, Safaa; Hoffman, Steven J.
Abstract: Global antimicrobial resistance (AMR) is currently governed by a decentralized regime complex composed of multiple institutions with overlapping and sometimes conflicting principles, norms, rules, and procedures. Such a decentralized regime complex provides certain advantages and disadvantages when compared to a centralized regime. A pandemic instrument can optimize the regime complex for AMR by leveraging the strengths of both centralization and decentralization. Existing climate treaties under the UNFCCC offer lessons for achieving this hybrid approach.